Ethical Perspectives and Theoretical Foundations of Punishment in Criminal Justice Systems - Kinslin, Greeshma (Journal of Social Science and Humanities, 2025)
This paper explores the ethical perspectives and various theories of punishment in the context of criminal justice. It discusses retributive, preventive, and reformative theories, analyzing their implications and effectiveness. The study aims to provide a comprehensive understanding of how different punishment philosophies impact crime prevention and offender rehabilitation.